FACTORS CAUSING AVERSION TO MATHEMATICS AMONG GRADE 12 STUDENTS IN PRIVATE SCHOOL IN THE MUNICIPALITY OF TAMPARAN PROVINCE OF LANAO DEL SUR, PHILIPPINES - Hassan S. Gandamra,; Bartolome L. Cagas, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigated the factors causing aversion to mathematics among grade 12 students of a private school in the municipality of Tamparan, Lanao del Sur, Philippines, enrolled in the school year 2023-2024. One hundred fifty (n=150) grade 12 students were surveyed using the Causes of Students’ Aversion in Mathematics Questionnaire (CSAMQ) developed by the authors. The following two questions guide the investigation: 1) What are the causes of students’ aversion to mathematics? 2) What are the students’ levels of aversion to mathematics? Students’ aversion to learning mathematics was hypothesized as caused by the nature of mathematics, the teacher, and student factors. On the causes of aversion, students declared that of mathematics factors (40.65%) and the teacher factors (56.3%) do not cause aversion, while the student factors (39.26%) cause aversion among them. On the level of aversion, students have a low level of aversion in mathematics due to the nature of mathematics factors (40.65 %) and teacher factors (56.3%), while having a high level due to student factors (39.26%). The results underscore the need to reduce the causes of aversion among students due to teachers’ teaching practices and students’ learning attitude, study practices, and personality characteristics of both teachers and students.